Language Policy and Planning: Diglossia in Indonesia - Nurhadi Hamka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2022)
Language policy is strongly connected with language planning, and that one cannot be discussed without included the other. This article will mainly discuss language policy and planning in Indonesia, especially the diglossic situation. The discussion is departed at a wider definition of language policy and planning. After that, I directly discuss the dynamics of local languages in Indonesia regarding the language policy and planning. The third, the discussion is about diglossia and diglossia-leakage that occurred in Indonesia. Afterward, in the fourth section, it talks about the domination and subordination of language. And, finally some research recommendation regarding language domination and subordination